Kekuatan Bahasa Dalam Melestarikan Bangunan Cagar Budaya: Sebuah Pendekatan Kreatif - Arum Puspitasari (2025)
Language holds significant potential as a medium of cultural preservation. In functions not only as a tool of communication but also as a creative means to instill awareness, construct collective memory and strengthen the emotional bond between communities and their cultural heritage. In the context of safeguarding heritage buildings, language serves as an instrument that preserves not only the material aspects but also the symbolic meanings embedded within them. The background of this study stems from the fact that preservation efforts have largely emphasized physical aspects such as conservation and regulation, while the cultural and symbolic dimentions remain less explored. The purpose of this research is to analyze the power of language, both oral and written, in sustaining the existence of heritage buildings through creative, narratives, myths, legends and digital storytelling. The theoretical foundation draws upon Malinowski and Radcliffe-Brown’s functionalist perspective on the social role of myths, Roland Barthes’ semiotics on language as a system of signs, Halbwachs’ concept of collective memory and Edward T. Hall’s theory of cultural communication. This research employes a descriptive qualitative approach using literature review, narrative analysis and case studies of heritage sites such as historical forts and palaces. The findings reveal that language has a persuasive power to foster a sense of ownership, pride and responsibility among communities. Folklore, myths and historical narratives prove effective in raising public awareness, reinforcing collective identity and culvating emotional attachment to heritage buildings. Thus, language fungtions not only as a madium of cultural transmission but also as a cretive and effective strategy for haritage preservation in the modern era